(untitled) (Ocean and Coastal Research, 2022)
The ocean is a unique system connecting ecological, economic, social, and cultural components, through which goods and services regulate the planetary condition and support the development of mankind. However, its increasing use has followed the exponential growth of the global economic system, outpacing humanity’s ability to develop the knowledge necessary to establish a basis for its proper use. Hence, there is an added perception that our necessary knowledge about the functioning of the ocean for its appropriate planning and management, advances at a slow pace, with which the ocean would be losing quality and sustainability. Systemic views of the ocean tend to highlight dominant components and processes instead of structural details, establishing a quality shortcut to the knowledge where society can understand current and future ocean conditions. To achieve the desired ocean health and sustainability, we propose the formation of a base of knowledge of the marine and coastal environments, capable of supporting best practices and policies for planning and management. We drew from the interdisciplinary research developed by the Brazilian research group “Ecosystem-Based Marine and Coastal Management (Eco-MCM), ” which has been developing projects based on three fundamental steps: (1) systemic analysis of the marine and coastal environments, highlighting their ecosystems, ecosystem services, social and economic benefits produced by the services and the stakeholders benefited; (2) modeling of the studied systems, and (3) propositional phase to incorporate models to support the practices and policies for their planning, management, and governance. As such, they are aligned with the United Nations Decade of Ocean Science for Sustainable Development (2021-2030) challenges and outcomes.